PENYULUHAN MANAJEMEN USAHA, KEMASAN DAN PEMASARAN PRODUK MAKANAN OLAHAN IKAN UNTUK MENINGKATKAN KESEJAHTERAAN - Ichwani, Arief; Fauzi, Yasir Muharram; Anwar, Nizirwan (LPPM Universitas Bina Bangsa, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in Indonesia's economy, contributing more than 60% to the Gross Domestic Product (GDP) and creating over 97% of employment opportunities. One promising sector is the processed fish food industry, which has great potential both in domestic and international markets. However, many business players, including BUMMas Inspirasi Negeri, have yet to fully maximize this potential due to limitations in business management and a lack of innovation in product packaging and marketing. Attractive and functional packaging, along with good management, has proven to be key factors in enhancing competitiveness, extending product shelf life, and strengthening brand identity. Additionally, consumers are increasingly drawn to unique packaging innovations. In the face of challenges such as market competition and limited technology, digital marketing has become essential for promoting products. Therefore, training on business management, packaging, and marketing through digital channels is crucial. The Community Service Team (PKM) from Esa Unggul University and Ma’soem University conducted a workshop for BUMMas Inspirasi Negeri, focusing on the processed fish food industry, to help business owners enhance professionalism, creativity, and product competitiveness. The outcomes of this workshop have improved the members' understanding of business management, upgraded packaging quality, expanded market reach, facilitated transactions through digital technology, and encouraged the economic well-being of the business operators